Elite athletes coping with depression: A qualitative study - Lebrun, F.; MacNamara, A.; Collins, D.; Rodgers, S. (Journal of Clinical Sport Psychology, 2019)
Little is known about the coping strategies used by elite athletes suffering from mental health issues. Therefore, this study examined coping strategies implemented by elite athletes facing clinical depression. Semi-structured interviews were conducted with four elite athletes and analysed using Interpretative Phenomenological Analysis (IPA). Results present a broad picture of how elite athletes tried to cope with depression using a range of coping strategies. Among the different strategies highlighted, talking, seeking professional help and social support were particularly emphasized by the participants. Surprisingly, however, only one participant reported transferring the skills and strategies learned on her way to the top to many other aspects of her everyday life such as coping with her depression. Findings, therefore, suggest that athletes should be encouraged to transfer and make the most of the skills learned throughout their sport career to deal with their daily life. Future research perspectives and implications are discussed.